People Development System as a Pillar in Implementing Lean For Public Sector - A. P., Puvanasvaran (Penerbit Universiti, 2011)
Human factor plays an important role in ensuring lean process management to be successful and provides good proposition for the success of the organization in the long run. One of the main elements of people is their problem solving capability in identifying and eliminating wastages. The purpose of this paper was to review the challenges faced by the public sector and find the solution to integrate Lean concept in their daily business. Beside that the paper also proposed the conceptual framework of people development system which can help public sector to enhance employees’ capability in identifying and eliminating wastages continuously and effectively.